Standards for the Language Competence of French Immersion Teachers: Is There a Danger of Erosion? - Veilleux, Ingrid; Bournot‐Trites, Monique (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
We examined standards used by Canadian universities and British Columbia school districts to verify the language competence of French Immersion (FI) teachers in a time of teacher shortage, confirmed by 56 per cent of school districts surveyed. Parents and Directors of Human Resources agreed on their minimum expectations about French teachers’ qualifications in FI schools. We found no guarantee for this level of teachers’ competence because of heterogeneity in universities and school districts language measures and lack of validity and reliability for many of those measures. This may result in lowering teaching quality in FI programs. Key words: teachers’ qualifications, parents’ expectations, language testing, second language, teacher shortage Nous avons examiné les standards utilisés par les universités canadiennes et les commissions scolaires de Colombie‐Britannique pour vérifier la compétence linguistique des enseignants d’immersion française (IF) alors qu’une pénurie d’enseignants a été confirmée par 56% des commissions scolaires interrogées. Les parents et les directeurs des ressources humaines ont des attentes minima similaires au sujet des qualifications des enseignants en IF. Cependant, le niveau de compétence n’est pas garanti à cause de l’hétérogénéité des mesures employées et de leur manque de validité et de fiabilité dans bien des cas. La qualité de l’enseignement dans les programmes d’IF pourrait s’en ressentir. Mots‐clés : qualifications des enseignants, tests de compétence langagière, pénurie d’enseignants, attentes des parents d’élèves